Aplicación web móvil híbrida para un sistema generador de encuestas socioeconómicas aplicando la metodología modelo mobile sprint - Girón Rivera, Michael Steven (2024)
The main objective of this document is to develop a hybrid mobile web application for a socioeconomic survey generating system applying the MOBILE SPRINT MODEL (MMS) methodology. In addition to the development and application of the program, it is also analyzed how it influences through the different phases that the methodology has in the implementation of the project, determining how many benefits it can generate. Also, the MMS allows us to generate an optimal planning to qualify and quantify efficiently the available resources and the foreseen activities, of course in the coding since it helps to generate several quality tests before its later launching. The application must be attractive to the user and easy to use, because it will throw a lot of information, for this it is vital to create an interface for both the web and mobile application to ensure visual appeal but above all, give the user the ability to navigate within the application without major complications. The MMS methodology and ISO 27001 complement each other adequately in the development since both contribute to improving the quality standards of the product, such as validation, authentication, usability, interface design, accessibility, among others. This is very beneficial, since by having two districts’ methods to guarantee the quality of the system, we ensure that the analysis of the results obtains the best possible results.